2009
DOI: 10.4049/jimmunol.0801935
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-1 Is Regulated in Tuberculosis by a p38 MAPK-Dependent,p-Aminosalicylic Acid-Sensitive Signaling Cascade

Abstract: Mycobacterium tuberculosis (M. tb) must cause lung disease to spread. Matrix metalloproteinases (MMPs) degrade the extracellular matrix and are implicated in tuberculosis-driven tissue destruction. We investigated signaling pathways regulating macrophage MMP-1 and -7 in human pulmonary tuberculosis and examine the hypothesis that the antimycobacterial drug p-aminosalicylic acid acts by inhibiting such pathways. In primary human macrophages, M. tb up-regulates gene expression and secretion of MMP-1 (interstitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…P-amino-salicylic acid, used to treat TB for 60 years but with a poorly defined mechanism of action, inhibits MMP-1 secretion by M. tuberculosis-infected macrophages (37), suggesting that an established treatment for TB may act by limiting tissue destruction. We demonstrate that Ro32-3555, a compound that has been used in phase III clinical trials for arthritis (11), can suppress M. tuberculosis-driven MMP-1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…P-amino-salicylic acid, used to treat TB for 60 years but with a poorly defined mechanism of action, inhibits MMP-1 secretion by M. tuberculosis-infected macrophages (37), suggesting that an established treatment for TB may act by limiting tissue destruction. We demonstrate that Ro32-3555, a compound that has been used in phase III clinical trials for arthritis (11), can suppress M. tuberculosis-driven MMP-1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemistry of the lung extracellular matrix predicts that matrix metalloproteinases (MMPs) will be the dominant proteases driving lung matrix destruction in TB (12). We have shown that MMP-1 is a key collagenase up-regulated in patients with TB (13,14), and MMP-1 expression is suppressed by p-amino salicylic acid, an antituberculous agent used for 70 years but with an incompletely understood mechanism of action (15). In the zebrafish model, MMP-9 regulates monocyte recruitment to the granuloma (16), indicating that MMPs both modulate the immune response to Mycobacterium tuberculosis (Mtb) and drive pathology (17).…”
mentioning
confidence: 91%
“…Monocyte-derived primary human macrophages were infected with Mtb H37Rv as described (15), and this strain was used in all cellular experiments. Primary human bronchial epithelial cells (Lonza, Slough, UK) were cultured and stimulated with conditioned media from Mtb-infected monocytes (CoMtb) and A549 cells transiently transfected as described (22).…”
Section: Cell Culture Experimentsmentioning
confidence: 99%
“…Both the p38 and extracellular signal-related kinase/mitogenactivated protein kinase (MAPK) pathways are critical in regulating MMP secretion in multiple cell types, both as a result of direct infection and intercellular networks [35,36,63,66,67]. Although p38 MAPK pathway activation has multiple effects, including mRNA stabilisation, in primary human macrophages one critical downstream effector is the cyclooxygenase (COX) pathway.…”
Section: Regulation Of Mmp Expressionmentioning
confidence: 99%